A Photovoice Project: Urban Elementary Girls’ Perspectives on Physical Activity - Graves, Myia L.; Nabors, Laura A.; Bernard, Amy L.; Vidourek, Rebecca A. (International Journal of Child Health and Nutrition, 2019)
Photovoice is a community-based participatory research method where participants can showcase their life experiences through photography. The objective of this study was to have adolescent girls attending an after-school program use photovoice to represent their perceptions of physical activity practices. Photovoice was used to allow adolescent girls to express their perspectives, through photographs and narratives, of their personal and community strengths and concerns related to their involvement in physical activity. The phenomenological methodology was used as a framework for the study. Qualitative analyses were conducted throughout the research process. Constant comparison was used to analyze the focus group, scrapbook data, and notes recorded by the author to determine key themes and ideas. Participants for the study included 14 girls attending a school in an urban area. Benefits of physical activity as provided by the girls in their personal lives and the community included: understanding activity contributed to wellness, increased social opportunities, and the school as a hub of activities. Personal and community barriers to physical activity included: lack of neighbourhood safety, being involved in other sedentary activities, parental rules restricting outside play, outside conditions, personal choices to not exercise, and a lack of opportunity to exercise. Potential ways to increase physical activity among these participants are to create more group games and activities at the after-school program daily. Involving parents in activities with the girls at home may increase physical activity levels while at home.